Pauline Christianity - Ziesler, J. A. (Oxford University Press, 1990)
Dr Ziesler's starting point is St Paul's view of Jesus Christ as marking the end of an era and the beginning of a new world and a new humanity.
Keywords: Bible. -- Epistles of Paul -- Theology.; Paul, -- the Apostle, Saint -- Influence.; Bible. -- Épîtres de Paul -- Théologie.; Paul, -- the Apostle, Saint; Bible. -- Epistles of Paul; Paulus -- Apostel, Heiliger; Paulus (Apostel); Church history -- Primitive and early church, ca. 30-600.; Christianity -- History -- Primitive and early church, ca. 30-600.; Église -- Histoire -- ca 30-600 (Église primitive); RELIGION -- Biblical Studies -- New Testament.; RELIGION -- Biblical Studies -- Paul's Letters.; Church history -- Primitive and early church; Influence (Literary, artistic, etc.); Theology; Theologie; Nieuwtestamentische theologie.; Brieven van Paulus.; Vroege christendom.; 30-600